Development of a hythane based cogeneration system integrated with gasification and landfill subsystems - Sorgulu, Fatih; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, a hythane (which is known as a blend of methane and hydrogen) based combined cycle integrated with gasification and landfill subsystems (digesters) is proposed to provide electricity and heat for buildings. The system is analyzed for the various wastes and evaluated in terms of energy, exergy and the environmental impact. The parametric studies are conducted for the ambient temperature and fractions of hydrogen in hythane. By designing this kind of system, it is aimed to provide an effective solution to dispose of the waste. Biomass-based energy systems have many advantages in terms of energy demand and environmental issues. Not only supply heat and electricity but also dispose of wastes are very critical issues. In Istanbul, the biggest city in Turkey, more than 18,000-ton municipal waste is collected and treated per day. This enormous amount of waste needs to recover for useful outputs, such as fuels, electricity, heating, and cooling. The overall energy and exergy efficiencies of the integrated system are calculated as 76.30% and 35.17%, respectively. The required mass flow rate of 0.13 kg/s and the lower heating value of 52,153 kJ/kg hythane are calculated to generate 3.5 MW electricity and 1.52 MW heat rate to the residential area. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Hythane; Methane; Biomass; Exergy; Sustainable energy; WASTE; Thermodynamics; Energy & Fuels